The Effect of Chicken Bone Powder Supplementation during Pregnancy and Lactation on the Calcium Level of Rat Pups’ Teeth - Atmokotomo, P; Arlan, A; Sitosari, H; Haniastuti, T; Linggar Jonarta, A (KnE Life Sciences, 2019)
Calcium is an important mineral needed during tooth and bone development. Additional calcium intake from the diet may help to maintain calcium level during pregnancy and lactation. Chicken bone contains high calcium so it can be used as a natural calcium source due to its bioavailability. This study was conducted to investigate the effect of chicken bone powder during pregnancy and lactation period on the calcium level of Sprague Dawley pups’ teeth. Six female Sprague Dawley were divided into treatment and control group. The treatment group was given chicken bone powder supplementation from the first day of pregnancy up to the fifteenth day after the delivery of the pups while the control group was given CMC-Na suspension by intragastric administration method. On the 15 d after the delivery, the pups were decapitated and the teeth from both groups were collected. The calcium level then assayed by atomic absorption spectrophotometry (AAS) method and the data were analyzed with an independent t-test. The result from the study showed that the calcium level of the teeth from the treatment group was significantly higher than the control group (P = 0.003). This result suggests that the administration of chicken bone powder during pregnancy and lactation period of mother rat could increase the calcium level of Sprague Dawley pups’ teeth. Keywords: Chicken bone powder, Tooth calcium level, Pregnancy and lactation period, Sprague Dawley, Tooth development.